Application of zathura mathematics media to improve critical thinking ability - Nurkhofifah, Watini; Choirudin, Choirudin; Ningsih, Eka Fitria; Anwar, M. Saidun; Setiawan, Agus (Universitas Muhammadiyah Malang, 2024)
This study aims to increase students' critical thinking ability through applying Zathura Mathematics media. This research is quantitative research with an experimental approach. The research was conducted at the MTs Mathla'ul Anwar Rawa Selapan school with samples from classes VII B and VII C. The data collection instrument was a validation sheet—assessment, sheet posttest, and documentation. The average value of the results Study or the mean is 47.68 and 57.59. Therefore, descriptive statistics can conclude that there is a difference between learning using Zathura Mathematics media and not using media. Sig value. (2-tailed) of 0.086 > 0.05, it is concluded that H0 is accepted and H1 is rejected, which means there is no significant difference between learning using Zathura Mathematics media and learning not using media. This research concludes that there is no significant difference between learning and using Zathura Mathematics media and learning without media. External variables may influence the research results but cannot be controlled by the researcher. However, descriptive statistics can conclude that there is a difference between learning using Zathura Mathematics media and not using media. With the results of this research, it can be said that there is an influence on the use of learning media. Zathura Mathematics can improve students' critical thinking abilities.